2016
DOI: 10.1155/2016/5941279
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Obesity in Sepsis Outcome among Critically Ill Patients: A Retrospective Cohort Analysis

Abstract: Background. The objective of this study was to assess the correlation between sepsis, obesity, and mortality of patients admitted to an Intensive Care Unit (ICU). Subjects and Methods. Data of all patients admitted to the ICU of a tertiary hospital during a 28-month period were retrospectively analyzed and included in the study. Results. Of 834 patients included, 163 (19.5%) were obese, while 25 (3.0%) were morbidly obese. Number of comorbidities (P < 0.001), bloodstream infection (P  0.033), and carbapenemase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 24 publications
4
42
3
1
Order By: Relevance
“…Furthermore, our findings suggested that there was a trend towards extended periods of ventilation, longer ICU and hospital LOS in obese patients, as prior studies have reported (Papadimitriou-Olivgeris et al, 2016;Sakr et al, 2015). This finding is mainly attributed to higher risks of nosocomial infection and respiratory complications (Sakr et al, 2008) that are associated with obesity.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, our findings suggested that there was a trend towards extended periods of ventilation, longer ICU and hospital LOS in obese patients, as prior studies have reported (Papadimitriou-Olivgeris et al, 2016;Sakr et al, 2015). This finding is mainly attributed to higher risks of nosocomial infection and respiratory complications (Sakr et al, 2008) that are associated with obesity.…”
Section: Discussionsupporting
confidence: 72%
“…Regarding the association of BMI and hospital infection, the present study demonstrated that the patients with BMI < 18.5 had the highest rate of hospital infection, while the normal-BMI patients had the lowest rate. A retrospective cohort study by Papadimitriou-Olivgeris et al supports the current results [34]. The study, focused on the role of obesity in the prognosis of sepsis patients, revealed that obesity had a direct impact on some morbidities, including bloodstream infection and Klebsiella pneumonia colonization, concluding that obesity affects sepsis upon ICU admission.…”
Section: Discussionsupporting
confidence: 81%
“…20 As previously discussed, multidrug resistance was scarce in our population, thus our findings may not be generalizable to countries with high percentages of multidrug-resistant pathogens. 17,21 Another limitation, was that we included only patients with bacteraemia and not patients with suspected infection or those with sepsis.…”
Section: Discussionmentioning
confidence: 99%